ALGORITHM OF TIME STAMPS DISTRIBUTION FOR DATA SYNCHRONIZATION OF VARIOUS MEASUREMENT SYSTEMS - Wajman, Radosław; Jaworski, Tomasz; Fiderek, Paweł; Banasiak, Robert (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2013)
The described in this paper research refer to the finished project which aimed to build the measurement system for phase distribution calculation and two phase flow structure identification based on 3D ECT system. In the frame of this work the metrological validation of the measurement system was done where many of various measurement technics were applied parallel. In order to analyse the measurement results, there was a need to design the unified service of time stamps distribution for measurement data synchronization. The measured data were collected with different speed. This paper presents the designed universal network algorithm of the time stamps distribution.